Estimation levels of CTHRC1and some cytokines in Iraqi patients with Rheumatoid Arthritis (Baghdad Science Journal, 2023)
Collagen triple helix repeat containing-1 (CTHRC1) is an essential marker for Rheumatoid Arthritis (RA), but its relationship with pro-inflammatory, anti-inflammatory, and inflammatory markers has been scantily covered in extant literature. To evaluate the level of CTHRC1 protein in the sera of 100 RA patients and 25 control and compare levels of tumour necrosis factor alpha (TNF-α), interleukin 10 (IL-10), RA disease activity (DAS28), and inflammatory factors. Higher significant serum levels of CTHRC1 (29.367 ng/ml), TNF-α (63.488 pg/ml), and IL-10 (67.1 pg/ml) were found in patient sera as compared to that in control sera (CTHRC1 = 15.732 ng/ml, TNF-α = 33.788 pg/ml, and IL-10 = 25.122 pg/ml). There was no significant correlation between the level of serum CTHRC1 and DAS28 (r = 0.046, P = 0.650), while there were positive significant correlations between the levels of serum CTHRC1 and CRP (r = 0.372, P = 0.0001), ACPA (r = 0.254, P = 0.01), TNF-α (r = 0.202, P = 0.044), and IL-10 (r = 0.260, P = 0.0001). The level of CTHRC1 (> 25.385 ng/ml) in combination with the levels of CRP and ACPA provided a good indication of RA prediction with sensitivity = 71.0%, specificity = 100.0%, accuracy = 0.71%, positive predictive value (PPV) = 100.0%, and negative predictive value (NPV) = 46.3%. The study showed a significant correlation between the levels of CTHRC1 and TNF-α, and IL-10. These molecules may play a prominent role in the diagnostic and etiology of RA